2023
DOI: 10.21037/apm-22-1256
|View full text |Cite
|
Sign up to set email alerts
|

First booster dose uptake of COVID-19 vaccine and disease-related factors in chronic obstructive pulmonary disease—a cross-sectional survey in Hungary

Abstract: Background: In chronic obstructive pulmonary disease (COPD), uptake of the coronavirus disease 2019 (COVID-19) booster vaccine is important, as they are more likely to develop serious complications. Our aim was to investigate the uptake rate of first booster vaccination against COVID-19 among COPD patients and to identify other related factors of vaccine uptake. Methods: We conducted a multicenter survey of COPD patients in Hungary by region: eastern, western and central ones from 15 November 2021. Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Based on a previous publication [33] and the relevant literature [25][26][27][28][29], a structured questionnaire was developed (Supplementary File S1). The questionnaire consisted of questions from different categories: (1) socio-demographic factors, such as age, gender, marital status, and educational background; (2) factors influencing health status, including smoking habits, previous medical conditions, self-assessed health, vulnerability level, and the vulnerability of family members; (3) information on their COVID-19 vaccination status, including the number of doses received and any side effects reported; (4) willingness to receive additional (booster) doses of the vaccine (yes/no); (5) attitudes and beliefs regarding the COVID-19 vaccine (20 items with questions of agreement or disagreement); (6) level of knowledge and questions about the impact of various factors on vaccine participation, such as religion, politics, science, media, and the anti-vaccine movement and whether they had received the influenza vaccination during the previous season; and (7) concerns regarding the possibility of getting infected with COVID-19.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a previous publication [33] and the relevant literature [25][26][27][28][29], a structured questionnaire was developed (Supplementary File S1). The questionnaire consisted of questions from different categories: (1) socio-demographic factors, such as age, gender, marital status, and educational background; (2) factors influencing health status, including smoking habits, previous medical conditions, self-assessed health, vulnerability level, and the vulnerability of family members; (3) information on their COVID-19 vaccination status, including the number of doses received and any side effects reported; (4) willingness to receive additional (booster) doses of the vaccine (yes/no); (5) attitudes and beliefs regarding the COVID-19 vaccine (20 items with questions of agreement or disagreement); (6) level of knowledge and questions about the impact of various factors on vaccine participation, such as religion, politics, science, media, and the anti-vaccine movement and whether they had received the influenza vaccination during the previous season; and (7) concerns regarding the possibility of getting infected with COVID-19.…”
Section: Data Collectionmentioning
confidence: 99%
“…Nevertheless, there is limited information regarding patients with COPD or asthma who hesitate to receive regular COVID-19 vaccinations. One recent study showed that the coverage of COVID-19 booster vaccination among patients with COPD was less optimal (62.45%) [29] than the target of 70% suggested by the World Health Organization (WHO) [30]. To the best of our knowledge, there have been no reports on the coverage of COVID-19 booster vaccinations among patients with asthma.…”
Section: Introductionmentioning
confidence: 99%